The Schoolscape of SMAN 1 Semarang: Patterns of Language Use and Global Identity - Al Basit, Afan Makhrus; Priyatmojo, Arif Suryo (PROJECT (Professional Journal of English Education), 2026)
This study investigates the schoolscape of SMAN 1 Semarang to understand its language patterns and underlying representations. Using a descriptive qualitative approach, data were collected through 151 photographic records of linguistic signs and an interview with the school's quality assurance officer. The findings reveal a predominantly bilingual environment, dominated by Indonesian-English signs (72 signs), followed by monolingual Indonesian (67 signs), while standalone English signs are extremely rare. The analysis indicates this landscape is primarily driven by top-down institutional policies (122 signs) rather than bottom-up initiatives from students and school organizations. Triangulated with the interview, the study concludes that English serves a symbolic, rather than purely pedagogical, function. It visually manifests the school’s global orientation, aligning with its international exchange program. Ultimately, the consistent pairing of English with Indonesian demonstrates a strategic institutional negotiation to project global prestige while complying with national language regulations and preserving local identity.